The Expansion of the Universe - Gimsa, Dr. Andreas (International Journal of Scientific Research and Management (IJSRM), 2020)
The expansion of the universe is explained, calculated and graphically displayed. The 3K background radiation is examined and interpreted as reflected and distributed stellar radiation. The role of entropy in cosmology is discussed. In our expanding universe it must remain constant. Physical quantities previously assumed to be constant are worked out to be variable. It is explained why the measured redshift is not due to an accelerated growth of the universe.